How are arts organizations responding to critique in the digital age?. (3rd May 2016) - Wiggins Johnson, Jennifer; Preece, Stephen B.; Song, Chanho
Abstract : Purpose: – Online communications have made critical reviews widely accessible, enabled a broader range of opinions to be heard, and led to increased critical dialogue among audiences. The purpose of this paper is to investigate how arts organisations' strategies for engaging with critique have evolved in the digital age. Design/methodology/approach: – This paper uses a content analysis of the online presence of 45 organisations. Based on the results, the organisations are classified into three different strategic approaches. The organisations' publicly available financial data are analysed to explain differences in the choice of strategic approach, and specific cases are used to better understand their strategic execution. Findings: – Organisations are engaging in three primary strategic responses: ignoring outside critique, presenting only positive reviews and ignoring or "spinning" negative reviews, and presenting all critique regardless of source or valence. The financial analysis suggests that the choice of strategic response varies across organisations of different sizes and approaches to advertising. Case analyses suggest that the strategy of presenting all critique has the potential to deepen audience engagement and value. Originality/value: – Previous research on critical reviews has focused on traditional media and the importance of the professional critic. This paper is the first to examine strategies for coping with the complex, multiple-voiced nature of critique in the current online environment. The findings suggest questions for future research and provide initial guidelines for organisations in determining a strategic approach to responding to critique.